Purple Hibiscus - Adichie, Chimamanda Ngozi (Kachifo Ltd, 2006)
Fifteen-year-old Kambili's world is circumscribed by the high walls and frangipani trees of her family compound. Her wealthy Catholic father, under whose shadow Kambili lives, while generous and politically active in the community, is repressive and fanatically religious at home. When Nigeria begins to fall apart under a military coup, Kambili's father sends her and her brother away to stay with their aunt, a University professor, whose house is noisy and full of laughter. There, Kambili and her brother discover a life and love beyond the confines of their father's authority. The visit will lift the silence from their world and, in time, give rise to devotion and defiance that reveal themselves in profound and unexpected ways.
Keywords: Fiction; Freedom